Quality Measurement and Patient Outcomes in Inpatient Behavioral Health: Assessing the Current Framework. Issue 6 (November 2021) - Nowlin, Rachel B.; Brown, Sarah K.; Ingram, Jessica R.; Smith, Johan R.
Abstract : ABSTRACT: Quality measurement across healthcare is undertaken with a goal of improving care and outcomes for patients; however, the relationship between quality measurement and patient outcomes remains largely untested, particularly in inpatient behavioral health. Using a retrospective quantitative design, we assessed 142 behavioral health organizations' quality data submitted to the Hospital-Based Inpatient Psychiatric Services and Inpatient Psychiatric Facility Quality Reporting programs from 2017 to 2018 and tested relationships between compliance on 16 quality measures and symptom improvement on patient self-report outcomes (SROs) at the facility level. Performance on many quality measures was negatively skewed (at least four have almost no room for improvement on average), and there was high interrelatedness between most quality measures. Nine of the assessed measures correlated with patient SROs but not in clear groupings. Findings indicate that an underlying organizational construct may be driving compliance rates on quality measures, but the measures are not linked to treatment outcomes as expected. We encourage an expansion of the current framework of behavioral health quality measurement beyond process and organization and suggest the addition of patient outcomes such as SROs as quality measures to directly assess patient improvement. Abstract : Supplemental Digital Content is Available in the Text.